The concept of forming a learning environment based on cloud services Google apps for education - L. I. Hladka; V. H. Hrytsenko (Academy of Cognitive and Natural Sciences, 2013)
The importance of e-learning for educational institutions is growing rapidly. Many students are creating their own learning environments to optimize their own learning process by combining various Web services with the connected organizers they find most convenient. "Cloud-based services offer educational institutions new dynamic, relevant eLearning applications based on the use of cloud technology - the latest Internet technology.